Causation and mnemonic roles: on Fernández’s Functionalism - Andonovski, Nikola (Estudios de Filosofía, 2021)
Debates about causation have dominated recent philosophy of memory. While causal theorists have argued that an appropriate causal connection to a past experience is necessary for remembering, their opponents have argued that this necessity condition needs to be relaxed. Recently, Jordi Fernández (2018; 2019) has attempted to provide such a relaxation. On his functionalist theory of remembering, a given state need not be caused by a past experience to qualify as a memory; it only has to realize the relevant functional role in the subject’s mental economy. In this comment, I argue that Fernández’s theory doesn’t advance the debate about memory causation. I propose that this debate is best understood as being about the existence of systems, which support kinds of interactions that map onto the relations dictated by (causal) theories. Since Fernández’s functionalism tells us very little about this empirical question, the theoretical gains from endorsing it are minimal.